Effect of silver nanoparticles synthesized from millingtonia hortensis on the antioxidant status in isoproterenol induced male wistar rats - R.SAVITHA,; U.SARASWATHI, (International Journal of Pharma and Bio Sciences, 2016)
Millingtonia hortensis is commonly found in southern Asia, Thailand and central India, which is used to treat many diseases. The present study is to evaluate the preventive effect of silver nanoparticles synthesized from Millingtonia hortensis on isoproterenol induced cardiotoxicity in male Wistar rats. Results indicated that the rats administered with silver nanoparticles synthesized from Millingtonia hortensis showed a significant increase in the levels of enzymatic antioxidants SOD, CAT, GPX and GST and non- enzymatic antioxidants Vit-C, E and GSH. A decreased level of LPO was observed after treatment with silver nanoparticles. Flavonoids, phenols, glycosides and alkaloids are the important phyto constituents found in the plant extract. The study concluded that Millingtonia hortensis enhanced the antioxidant status in isoproterenol induced cardiotoxicity in rats.